Variety of languages and strategies for submitting verbal and nonverbal meanings in the film doraemon stand by me 1 & 2 - Panduyoga, R. Bambang Satrio; Pratama, Agus Darma Yoga (Aksara: Jurnal Bahasa dan Sastra, 2023)
Doraemon Stand by Me 1 & 2 film. Japan and this film using animated images make researchers want to analyze and examine strategies for conveying verbal and nonverbal meanings with the variety of children's languages found in the study. The method used in this research is a qualitative approach and descriptive analysis techniques. The data sources in this study are the first and second Doraemon Stand by Me films. The research data used are thirty-nine data. The results of the study found that the variety of children's languages used in the film Doraemon Stand by Me 1 & 2 were shown using 10 suffixes, namely Yo, Wa, Ne, Na, Zo, Ya, Mon, Kke, I, No in the children's language variety in Indonesia. in Japanese based on the theory from Takahashi Tarou. Verbal and nonverbal meanings in films are conveyed using three strategies, namely aspects of speech and images, aspects of images and sound effects, and aspects of images and writing. Of these three strategies, the speech and image aspects were found, then the image and sound effects aspects were found, and the image and writing aspects were the least found. The strategy of conveying meaning is easier to understand and can have a psychological impact on the audience such as sad, happy, tense, and others to make the audience entertained. Keywords: Doraemon Stand by Me, Variety of Languages, Verbal Meaning, and Nonverbal Meaning